2022
DOI: 10.2298/botserb2202239e
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of phenolic compounds, in vitro antioxidant and enzyme inhibition activities of methanol and aqueous extracts of different parts of Glaucosciadium cordifolium

Abstract: The present study was designed to evaluate the biological potentials and phenolic composition of different parts of Glaucosciadium cordifolium, which is less investigated and known as a wild endemic species to Turkey. The antioxidant activity of the plant was determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2'-Azinobis-(3-Ethylbenzthiazolin-6-Sulfonic Acid) (ABTS), iron chelating capacity, and a ?-carotene / linoleic acid emulsion assay. The total phenol and flavonoid contents of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Our findings indicate that the used doses of GCEO suppress the activity of AChE, which was elevated by SCOP exposure. Recently, Eruygur et al [ 19 ] evaluated methanolic and aqueous extracts from different parts of Glaucosciadium cordifolium , such as roots, stem, leaves, and flowers, for their anti-AChE and anti-butyrylcholinesterase (BuChE) potential. Their results showed that all tested extracts displayed cholinesterase inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our findings indicate that the used doses of GCEO suppress the activity of AChE, which was elevated by SCOP exposure. Recently, Eruygur et al [ 19 ] evaluated methanolic and aqueous extracts from different parts of Glaucosciadium cordifolium , such as roots, stem, leaves, and flowers, for their anti-AChE and anti-butyrylcholinesterase (BuChE) potential. Their results showed that all tested extracts displayed cholinesterase inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that all tested extracts displayed cholinesterase inhibitory activity. Of these, the aqueous extract of roots and leaves showed the greatest anti-AChE activity while the methanolic extract of stems exhibited the highest anti-BuChE activity [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations